Pengaruh Informasi Telekomunikasi Handphone Terhadap Perkembangan Mental Sosial Siswa di SDN Tundakan - Annisa Milyani (Madrasah: Jurnal Pendidikan Madrasah, 2024)
At this time, the development of communication technology is very rapid because everyone is free to use it. The use of communication technology has a great influence on human life patterns, one of which is in terms of thought patterns and behavior. Social interaction skills also influence children's use of telecommunications (cellphones). The internet is a medium used to make it easier to access information. In several large cities in Indonesia, many schools have started to use the internet as an important means of conducting learning. There are several positive benefits that students can receive from using the internet, such as extracting information and telecommunications. This research aims to determine the influence of mobile telecommunication information on the social mental development of grade 3 students at SDN Tundakan. This research uses a quantitative approach. Data collection techniques used questionnaires and interviews. The sample in this research was all 3rd grade students at SDN Tundakan, totaling 17 students. Data analysis techniques use statistical methods. The research results show that telecommunications information has a moderate effect on students' social mental development.